Accounting principles - Hermanson, Roger H.; Edwards, James Don.; Salmonson, R. F. (Plano, Texas: Business Publications, 1983)
This book is intended for use in the year introductory accounting courses. It served a foundation for subsequent courses in accounting and business.
Includes index.
Includes bibliographical references: p. 1068.
ne 13/07/2018
Loans
Keywords: Accounting